Digital storytelling as a motivating tool for promoting children's literature to the grade1 students of Tandang Sora Elementary School - Abao, Nonalu Sareena A. (2014)
Storytelling is a big part of a person's childhood and everyone has their own share of childhood stories. The stories may be from original books bought from bookstores or given by relatives. There are also stories which were created from a parent or guardian's imagination. Storytelling, like childhood, has also developed from traditional to digital. In line with this, the study focused on digital storytelling format and its use as a motivating tool for promoting children's literature.